Investigating Self-Assessment Integrated into E-portfolio in a Writing Activity - Abbas, M. Fadhly Farhy; Ningsih, T. Reni Widia (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Writing is one of the four main skills in English. Technological developments occur so rapidly in the world of education, especially in online learning as it is today which requires most universities to use E-Portfolio in its media writing activities such as Blogger. Blog refers to "Weblog", it means one type of website or online journal that contains displaying information from various sources and contains content such as articles, text, photos, videos, and links. In addition, in online learning self-assessment has been set so that students can find out their own abilities in writing activities. This research aims to determine student perceptions of self-assessment integrated with e-portfolios in writing activities. This research was a qualitative research with a narrative inquiry design. The results from this research revealed that some students showed good view about the use of e-portfolio in Blogger media because it can be accessed by anyone who is writing works. Based on self-assessment, the views of some students were positive because before publishing writing on Blogger, students could correct their writing in terms of topic ideas, vocabulary, grammar, and mechanics. In conclusion, through self-assessment students can know their ability to write, can assess themselves and think more creatively. The e-portfolio that has been implemented can facilitate student activities in writing without a time limit and it can be accessed anytime and anywhere, very useful for students during online learning.